Religious Moderation and Family Resilience in the City of Malang, Indonesia: The Historical Perspectives of the Islamic Law - Fadil, Fadil; Marwinata, Pepy; Jannah, Shofiatul; Siroj, A. Malthuf (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Religious moderation is a moderate attitude or perspective in religion that is fair and balanced. A moderate mindset and behavior in the family is very significant for married couples to avoid things that can damage the honor and dignity of the family. The research method used is an empirical legal study with an approach to the history of Islamic law. Data was collected through in-depth interviews with a number of informants namely, academics, housewives, teachers and self-employed people. While document studies are carried out by analyzing journal articles, books and various references related to the discussion. The research found that a moderate religious perspective and attitude are critical for family life. Family resilience strategies include belief systems, organizational processes, communication processes, and problem solvers. Among the materials that are very important for strengthening religious moderation in the family are tolerance, leadership in the family, division of roles in the family, equal relations between a husband and a wife, respect for the existence and quality communication of all family members, and cultivating negotiation in decision-making, And no less important is a moderate religious understanding. In terms of the Islamic law history, several families, such as the Prophet Ibrahim’s family, the Imran family (Alu Imran), and the Prophet Muhammad PBUH, can be used as examples of cultivating the true values of monotheism, humanity, social solidarity, and even purity and self-respect. Meanwhile, in Indonesia, the family of Hadaratus Sheikh KH. Hasyim Asyari, the founder of Nahdlatul Ulama can be used as an example who gives birth to children and grandchildren and even families who have a sense of nationalism, religion, humanism, pluralism and social solidarity.